Pyramidal ownership structure, dividend policy and value relevance of earnings information in Malaysia public listed firms / Irfah Najihah Basir Malan - Basir Malan, Irfah Najihah (Institute of Graduate Studies, UiTM, 2018)
This study provides empirical evidence on the pyramidal ownership structure, dividend policy as governance mechanism on agency problem and value relevance of earnings information in Malaysia public listed firms. For determinants of pyramid structure, all variables with exception to financial institution holding are significant at 1% significance level. The other variables such as cash and dividend payout ratio are insignificant. Meanwhile, the variables such as pyramid structure, risk, size, capital expenditure, debt, dividend payout ratio and liquidity are among the factors that significantly affect the corporate value as well as the dilution of minority interest at 1% and 5% significance level respectively. The effect of pyramid firms on corporate value is more pronounced when the pyramid firms are segregated into high cash flow right (CFR) ratio firms and low CFR ratio firms. For high CFR ratio firms, only four variables are significant which are capital expenditure, duality, stock liquidity and size. For low CFR ratio firms, the variables such as pyramid firm, size, capital expenditure, debt ratio, dividend payout ratio, duality and stock liquidity posit significant relationship with corporate value. The other three variables such as risk, cash and financial institution holding as second largest shareholders are insignificant…